2018
DOI: 10.1016/j.celrep.2018.03.090
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Reach Goals in Depth and Direction from the Parietal Cortex

Abstract: The posterior parietal cortex is well known to mediate sensorimotor transformations during the generation of movement plans, but its ability to control prosthetic limbs in 3D environments has not yet been fully demonstrated. With this aim, we trained monkeys to perform reaches to targets located at various depths and directions and tested whether the reach goal position can be extracted from parietal signals. The reach goal location was reliably decoded with accuracy close to optimal (>90%), and this occurred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 44 publications
(76 reference statements)
7
35
0
Order By: Relevance
“…The results therefore support a switch from a visual code to a more motor-related one or, alternatively, the superimposition of motor-related and proprioceptive information with previous underlying visual-related inputs. Similar results were recently found in V6A using a decoding analysis; the authors reported an evolution of visuo-to-motor coding during the execution of reaching and grasping ( Filippini et al., 2017 , 2018 ). Moreover, the stability of the correlations found in most epochs is reminiscent of the stability of a mixed body/hand reference frame found in V6A ( Hadjidimitrakis et al., 2020 , Piserchia et al, 2017 ).…”
Section: Discussionsupporting
confidence: 86%
“…The results therefore support a switch from a visual code to a more motor-related one or, alternatively, the superimposition of motor-related and proprioceptive information with previous underlying visual-related inputs. Similar results were recently found in V6A using a decoding analysis; the authors reported an evolution of visuo-to-motor coding during the execution of reaching and grasping ( Filippini et al., 2017 , 2018 ). Moreover, the stability of the correlations found in most epochs is reminiscent of the stability of a mixed body/hand reference frame found in V6A ( Hadjidimitrakis et al., 2020 , Piserchia et al, 2017 ).…”
Section: Discussionsupporting
confidence: 86%
“…It is worthwhile to notice that we used the entire recorded populations without any preselection. In this way, we were able to reproduce the same sampling criteria that would fit with prosthetic applications, where task-related and unrelated neurons are used 2426 .…”
Section: Discussionmentioning
confidence: 99%
“…Although, at present, a comparative study on the relative weight of the parameters of prehension in the different areas of the medial PPC is still lacking, it seems that PRR and PEc are involed in encoding spatial parameters for reaching and AIP in the encoding of object-oriented pragmatic actions, with V6A well suited to coordinate arm movements and grasping 19 . Decoding approaches showed that V6A can be a good source for decoding directional signals for reaching 24 and recently neural signals from V6A have been shown to be suitable for decoding hand shaping useful to implement brain machine interfaces to optimally guide prehensile actions 52 . The dimension reduction performed in the present study represents a general frame of the functional properties of the medial posterior parietal cortex that may be essential for improving computational efficiency in handling massive amounts of neural data for application in neuroprosthetics 53,54 .…”
Section: Discussionmentioning
confidence: 99%
“…Mixing of signals has also been observed at another level of movement control. The distance and direction of reach goals, which were considered to have independent neuronal substrates (Crawford et al, 2011), were encoded by largely overlapping neuronal populations in V6A and PEc (Hadjidimitrakis et al, 2014a, 2015; Filippini et al, 2018). Furthermore, PRR neurons can simultaneously encode multiple potential movement goals (Baldauf et al, 2008; Klaes et al, 2011), thus further illustrating the richness of the selectivity.…”
Section: Functional Response Properties In Individual Regions Of the mentioning
confidence: 99%